CODIFICATION OF THE NEW HUNGARIAN CODE OF CRIMINAL PROCEDURE – EVALUATION OF UNLAWFULLY OBTAINED EVIDENCE - Gacsi, Anett Erzsebet (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
This article analyzes the concept of the new Hungarian Code of Criminal Procedure, adopted February 11, 2015. Details revealed codifying basic principles: efficiency, speed, simplicity, modernity, consistency and dedication. Submitted proposals on changes and amendments to the concept of the new Hungarian Code of Criminal Procedure.